2015
DOI: 10.1039/c5cp01871d
|View full text |Cite
|
Sign up to set email alerts
|

What is the primary mover of water dynamics?

Abstract: Even today, the H-bonded cluster structure of water still stands as a major point of debate in the science of liquids. Much of this discussion is devoted to understand its dynamic nature. This has a direct impact on deciphering the many anomalies of water such as its exceptional heat capacity. Of these properties, dielectric permittivity and relaxation are of particular interest. The argument rages over whether the almost Debye-like character of the dispersion is the result of the reorientation of an apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Moreover, as suspected since long [19] and recently clearly revealed by broadband spectra extending into the THz range [8,15,18,20,21,22,23,24], at the high-frequency flank of the dominating 20 GHz loss peak (between about 300 GHz and 2 THz), excess intensity is detected, indicating contributions from a faster dynamic process. It shows up as a second, more shallow power law, superimposed to the  --1 decrease found for a Debye relaxation [ Fig.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Moreover, as suspected since long [19] and recently clearly revealed by broadband spectra extending into the THz range [8,15,18,20,21,22,23,24], at the high-frequency flank of the dominating 20 GHz loss peak (between about 300 GHz and 2 THz), excess intensity is detected, indicating contributions from a faster dynamic process. It shows up as a second, more shallow power law, superimposed to the  --1 decrease found for a Debye relaxation [ Fig.…”
Section: Introductionmentioning
confidence: 65%
“…It was recently pointed out [23] that the HFPL in dielectric spectra of water closely resembles the so-called excess wing (EW) found in dielectric loss spectra of many supercooled liquids [29,30,31]. This phenomenon is often assumed [32,33,34,35,36,37] to arise from a so-called  relaxation [38], partly submerged under the dominating  peak.…”
Section: Introductionmentioning
confidence: 86%
“…This function was recently used by Ishasi et al to fit the high frequency excess in water. 8 A cutoff frequency ω c is required, since otherwise this expression violates the Kramers-Kronig relations. In our experiments with this fit function, we found this cutoff could be ignored.…”
Section: Fitting the High Frequency Excessmentioning
confidence: 99%
“…6? In this paper we focus on the dielectric relaxation of water, about which an enormous literature already exists, including several recent detailed theoretical studies. [7][8][9][10][11] In our review of this literature, we found a lack of agreement on the molecular origins of the Debye relaxation and further disagreement on how to fit excess response on the high frequency side of the Debye relaxation, which historically had been fit with a secondary Debye relaxation. Some authors relate Debye relaxation to particular translational and/or rotational motions of a single molecules after breaking one or more hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the main component of blood is water, the dielectric properties of which have been recently studied extensively in Ref. . Here, the performance of previously introduced RF sensor is evaluated using aqueous glucose solutions, ranging from 40 to 400 mg/dL, as shown in Figure A.…”
Section: Measurement Setupmentioning
confidence: 99%